2020
DOI: 10.3390/ijms21041544
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Interleukin-33-responsive Kidney Group 2 Innate Lymphoid Cells in Acute Kidney Injury

Abstract: Interleukin (IL)-33, a member of the IL-1 family of cytokines, is involved in innate and adaptive immune responses. IL-33 triggers pleiotropic immune functions in multiple types of immune cells, which express the IL-33 receptor, ST2. Recent studies have revealed the potential applications of IL-33 for treating acute kidney injury in preclinical animal models. However, IL-33 and IL-33-responding immune cells are reported to exhibit both detrimental and beneficial roles. The IL-33-mediated immunomodulatory funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…These cells release several inflammatory mediators in response to this binding (IL-33/ST2) [ 38 ]. For inflammation-associated AKI, IL-33 recruits immune cells and amplifies inflammatory responses during the first 24 h [ 39 ]. In the current study, a high level of IL-33 expression was present in the CLP group in the intertubular spaces, glomeruli, and around the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…These cells release several inflammatory mediators in response to this binding (IL-33/ST2) [ 38 ]. For inflammation-associated AKI, IL-33 recruits immune cells and amplifies inflammatory responses during the first 24 h [ 39 ]. In the current study, a high level of IL-33 expression was present in the CLP group in the intertubular spaces, glomeruli, and around the vessels.…”
Section: Discussionmentioning
confidence: 99%
“…It is released following tissue injury and cell death. Since its discovery, IL-33 has been implicated in the onset and progression of asthma [1], cardiovascular diseases, kidney injury [2,3], and allergic diseases [4], as well as in organ fibrosis [5,6]. IL-33 has also recently been associated with Alzheimer's disease (AD) and rheumatic heart disease [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…18 IL-33-expanded ILC2s have been shown to be protective in a number of models of kidney disease including ischemia-reperfusion injury (IRI) by us and others. [19][20][21] In contrast, another study suggested that IL-33 treatment caused more severe renal fibrosis in the IRI mouse model. 22 Here we assess the role of IL-33 in the development of IgA nephropathy in BAFF-Tg mice, and then demonstrate that ILC2s contribute to IgA production and subsequent glomerulonephritis using an ILC2 transfer model.…”
mentioning
confidence: 96%
“…IL-33 is released as a nuclear alarmin in response to tissue damage and triggers innate and adaptive immune responses by binding to its receptor, suppression of tumorigenicity 2 (ST2) 18 . IL-33–expanded ILC2s have been shown to be protective in a number of models of kidney disease including ischemia-reperfusion injury (IRI) by us and others 19 21 . In contrast, another study suggested that IL-33 treatment caused more severe renal fibrosis in the IRI mouse model 22 .…”
mentioning
confidence: 99%